Markers of oxidative stress in adipose tissue during Trypanosoma cruzi infection - Wen, Jian-Jun (Parasitol Res, 2014)
The protozoan parasite Trypanosoma cruzi causes Chagas disease. Cardiac and adipose tissues are among the early targets of infection and are sites of persistent infection. In the heart and adipose tissue, T. cruzi infection results in an upregulation of pro-inflammatory mediators. In the heart, infection is associated with an increase in the markers of oxidative stress. To date, markers of oxidative stress have not been evaluated in adipose tissue in this infection. Brown and white adipose tissues were obtained from CD-1 mice infected with the Brazil strain of T. cruzi for 15, 30, and 130 days post infection. Protein carbonylation and lipid peroxidation assays were performed on these samples. There was an upregulation of these markers of oxidative stress at all time-points in both white and brown adipose tissue. Determinants of anti-oxidative stress were downregulated at similar time-points. This increase in oxidative stress during T. cruzi infection most likely has a deleterious effect on host metabolism and on the heart.